A piezo-phototronic enhanced serrate-structured ZnO-based heterojunction photodetector for optical communication. Issue 6 (30th January 2019) - Xiong, Da; Deng, Weili; Tian, Guo; Gao, Yuyu; Chu, Xiang; Yan, Cheng; Jin, Long; Su, Yuhan; Yan, Wei; Yang, Weiqing
Abstract : The serrate-structured heterojunction interface can enhance the performance of a ZnO-based photodetector, which facilitated the application of optical communication. Abstract : ZnO-based heterojunction photodetectors have been widely used in various fields such as optical imaging and health monitoring. As for the traditional planar heterojunction interface, their limited optical absorption will place restrictions on the full photoelectric potential of ZnO nanorods, which severely restrains the commercial applications of ZnO-based photodetectors. Herein, using an intrinsically octahedral structure of p-type Cu2 O and one-dimensional ZnO arrays, the newly designed serrate-structured heterojunction was constructed, whose unique serrate-structured interface of ZnO/Cu2 O is highly conducive to the aggrandizing of optical absorption. The as-fabricated photodetector could achieve a high on/off ratio up to 1000 and an optimum photocurrent of 24.90 μA under 1.41 mW mm −2 (405 nm) illumination without bias voltage, which was 2.5 times higher than that of the planar-structured photodetector, and the response time was as quick as 1.6 ms. When the additional external strain was 0.39%, the performance was dramatically enhanced more than 5 times due to the synergism of the piezo-phototronic effect and the serrate-structured design. Based on this, we successfully developed designed photodetector arrays with an excellent optical communication performance of transmitting information. Prospectively, this kind of unique serrate-structured heterojunction design will open up a possible opportunity for high performance photodetectors based on structural engineering.